THE ROLE OF ISLAMIC LAW IN SHAPING SUSTAINABLE ECONOMIC MODELS: EVIDENCE FROM INDONESIA’S SHARIAH-COMPLIANT INVESTMENT MARKET - Dadin Solihin; Haziq Idris; Rinah Farah; Nurul Huda; Siti Hasanah (Yayasan Adra Karima Hubbi, 2025)
The global shift toward sustainable economic models has sparked interest in the potential of Islamic finance to promote ethical and environmentally friendly investments. Indonesia, as the world’s largest Muslim-majority country, has seen significant growth in its Shariah-compliant investment market. This study explores how Islamic law influences the development of sustainable economic models within this market. The research aims to analyze the role of Islamic law in shaping sustainable economic practices in Indonesia’s Shariah-compliant investment market, identifying key drivers, challenges, and opportunities for growth. A mixed-methods approach is employed, combining quantitative analysis of investment data from Shariah-compliant funds and qualitative interviews with industry experts, Shariah scholars, and investors. Data were analyzed using thematic analysis for qualitative insights and statistical tools for quantitative data. The findings reveal that Islamic law significantly influences sustainable economic practices by promoting ethical investments, risk-sharing, and environmental stewardship. Shariah-compliant funds in Indonesia increasingly prioritize green investments and social impact projects, aligning with global sustainability goals.